1993
DOI: 10.1530/acta.0.1290585
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucagon responses to insulin-induced hypoglycemia and arginine in spontaneous non-insulin-dependent diabetes mellitus (NIDDM) rats, Otsuka Long Evans Tokushima Fatty (OLETF) strain

Abstract: Plasma glucagon responses to insulin-induced hypoglycemia and arginine in spontaneous non-insulin-dependent diabetes mellitus (NIDDM) rats, Otsuka Long Evans Tokushima Fatty (OLETF) strain. Acta Endocrinol 1993;129:585-93. ISSN 0001-5598Pancreatic A-cell function in the newly developed Otsuka Long Evans Tokushima Fatty (OLETF) strain of non-insulin-dependent diabetes mellitus (NIDDM) rats was examined in relation to the morphological changes in their islets and the plasma glucagon responses to insulin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Comparison between the CCK-AR -/-mice and the OLETF rats reveals several important differences. The OLETF rats have increased body weight, are prone to diabetes mellitus, and develop pancreatic islet fibrosis with age relative to wild-type strains (31,(44)(45)(46). In contrast, we have shown that the CCK-AR -/-mice maintain normal weight, normal blood glucose levels, and have pancreatic islet morphology that is indistinguishable from wild-type controls.…”
Section: Figurementioning
confidence: 59%
See 2 more Smart Citations
“…Comparison between the CCK-AR -/-mice and the OLETF rats reveals several important differences. The OLETF rats have increased body weight, are prone to diabetes mellitus, and develop pancreatic islet fibrosis with age relative to wild-type strains (31,(44)(45)(46). In contrast, we have shown that the CCK-AR -/-mice maintain normal weight, normal blood glucose levels, and have pancreatic islet morphology that is indistinguishable from wild-type controls.…”
Section: Figurementioning
confidence: 59%
“…of central mediators (e.g., serotonin, neuropeptide Y, orexins, corticotropin-releasing hormone), as well as a number of peripheral peptides (e.g., leptin, gastrin-releasing peptide, and glucagon-like peptide 1) (54,55,(57)(58)(59). A line of rats, Otsuka Long-Evans Tokushima Fatty (OLETF), which was initially developed as a model of non-insulin-dependent diabetes mellitus (31,44), has recently been shown to lack CCK-A receptors because of a spontaneous deletion in the corresponding receptor gene (29,30). Comparison between the CCK-AR -/-mice and the OLETF rats reveals several important differences.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Male OLETF rats own innate polyphagia with rapid body weight gain and accumulation of intra-abdominal fats, leading to the development of hyperlipidemia and insulin resistance from twelve weeks of age (Kawano et al, 1992;Sato et al, 1995). The cumulative incidence of diabetes in male OLETF rats reaches 80-100% at twenty-four weeks of age (Ishida et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…WBN/Kob rats [15,23], OLETF rats [4], and Aly mice [14] are known to develop pancreatitis spontaneously, and experimental pancreatitis can be induced by ethanol feeding [24] or arginine injection [6] in rats or mice. These conditions have thus been utilized as models for human pancreatitis.…”
Section: Introductionmentioning
confidence: 99%